A Comparative Analyses of the Complete Mitochondrial Genomes of Fungal Endosymbionts in Sogatella furcifera, White-Backed Planthoppers. (9th June 2021) - Choi, Nak Jung; Xi, Hong; Park, Jongsun
Abstract : Sogatella furcifera Horvath, commonly known as the white-backed planthoppers (WBPH), is an important pest in East Asian rice fields. Fungal endosymbiosis is widespread among planthoppers in the infraorder Fulgoromorpha and suborder Auchenorrhyncha. We successfully obtained complete mitogenome of five WBPH fungal endosymbionts, belonging to the Ophiocordycipitaceae family, from next-generation sequencing (NGS) reads obtained from S. furcifera samples. These five mitogenomes range in length from 55, 390 bp to 55, 406 bp, which is shorter than the mitogenome of the fungal endosymbiont found in Ricania speculum, black planthoppers. Twenty-eight protein-coding genes (PCGs), 12 tRNAs, and 2 rRNAs were found in the mitogenomes. Two single-nucleotide polymorphisms, two insertions, and three deletions were identified among the five mitogenomes, which were fewer in number than those of four species of Ophiocordycipitaceae, Ophiocordyceps sinensis, Hirsutella thompsonii, Hirsutella rhossiliensis, and Tolypocladium inflatum . Noticeably short lengths (up to 18 bp) of simple sequence repeats were identified in the five WBPH fungal endosymbiont mitogenomes. Phylogenetic analysis based on conserved PCGs across 25 Ophiocordycipitaceae mitogenomes revealed that the five mitogenomes were clustered with that of R. speculum, forming an independent clade. In addition to providing the full mitogenome sequences, obtaining complete mitogenomes of WBPH endosymbionts can provide insights into their phylogenetic positions without needing to isolate the mtDNA from the host. This advantage is of value to future studies involving fungal endosymbiont mitogenomes.